Polarization properties of longitudinally inhomogeneous dichroic medium - Kolomiets, I.S.; Savenkov, S.N.; Oberemok, Ye.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Polarization properties of longitudinal inhomogeneous medium with linear and elliptical dichroism based on differential Jones matrix are considered. Properties of privileged polarizations have been analyzed. The integral Jones and Mueller matrices of media are obtained as a solution of the vector transfer equation. Orthogonalization properties of these classes of media are studied. Evolution of totally polarized light in longitudinal inhomogeneous medium with linear and elliptical dichroism has been analyzed.